Ma’had Ittiḥād al-Islām (Persis) 1984-1996 wa al-Ta’līm al-Qā’im ‘alā Da’āmah al-Mujtama’ - Toto Suharto (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2004)
This article aims to discuss the educational model and thinking developed by Persis, through discussion of at least three main issues, namely educational ideology, educational curriculum and the institutional form of Persis education.DOI: 10.15408/sdi.v11i1.655